2013
DOI: 10.3851/imp2413
|View full text |Cite
|
Sign up to set email alerts
|

Efavirenz, Tenofovir and Emtricitabine Combined with First-Line Tuberculosis Treatment in Tuberculosis–Hiv-Coinfected Tanzanian Patients: A Pharmacokinetic and Safety Study

Abstract: Coadministration of efavirenz, tenofovir and emtricitabine with a standard first-line TB treatment regimen did not significantly alter the pharmacokinetic parameters of these drugs and was tolerated well by Tanzanian TB patients who are coinfected with HIV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…In a relatively similar study design in south Indian patient populations, Ramachandran et al reported that even though C max and AUC 0–24 seemed to slightly but insignificantly decrease with RIF‐based cotreatment, they concluded that RIF coadministration did not significantly alter the PK parameters of EFV . Semvua et al reported a similar outcome in Tanzanian patients, although C max , C min , and AUC 0–24 were slightly but insignificantly lower during RIF cotreatment . No effects of RIF coadministration on plasma concentrations of EFV at C mid‐dose or C min were reported in Cambodian, South African, Thai, Ugandan, and Tanzanian patients .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In a relatively similar study design in south Indian patient populations, Ramachandran et al reported that even though C max and AUC 0–24 seemed to slightly but insignificantly decrease with RIF‐based cotreatment, they concluded that RIF coadministration did not significantly alter the PK parameters of EFV . Semvua et al reported a similar outcome in Tanzanian patients, although C max , C min , and AUC 0–24 were slightly but insignificantly lower during RIF cotreatment . No effects of RIF coadministration on plasma concentrations of EFV at C mid‐dose or C min were reported in Cambodian, South African, Thai, Ugandan, and Tanzanian patients .…”
Section: Discussionmentioning
confidence: 93%
“…These methods are more variable and less reliable than methods that determine PK parameters from multiple concentration values in a subject. Of studies that investigated the impact of RIF‐based anti‐TB treatment on PK parameters, a few involved healthy volunteers or pediatric patients or did not consider pharmacogenetic information . A study by Bertrand et al used sparse PK samples from 10 subjects collected 6 months after stopping RIF‐based anti‐TB treatment.…”
mentioning
confidence: 99%
“…Of the 14 studies conducted among adult patients that reported EFV concentrations on and off RH, 10 were in Africa and four in Asia. Notably, among the 10 adult studies conducted in Africa, six reported higher EFV concentration during RH coadministration compared to the off‐RH period, although the difference is highly variable, ranging from 3.7% to 33.3% across studies and countries . The remaining four adult African studies reported a lower EFV concentration while on RH, still with a difference that is highly variable, ranging from –16.3 to –33.3% .…”
Section: Resultsmentioning
confidence: 99%
“…In adults, EFV was systematically administered at a dose of 600 mg day –1 of which one study also had EFV 800 mg day –1 dose administered to a selected comparative group of patients . EFV was administered at bed‐time to improve the tolerability and reduce adverse events , except for four adult studies where it was taken in the morning and a 6‐month anti‐TB treatment was used and administered daily at recommended dosing in all studies except one with intermittent administration . Thirteen studies (59%) reported EFV concentrations on and off RH within the same patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation